Why Malaysia’s ‘Ir.’ is Stagnating? - Wan Sharuzi, Wan Harun (UMPSA, 2025)
At first glance, the Board of Engineers Malaysia (BEM) appears to be a resounding success. Between 2009 and 2024, the number of engineers on its books more than tripled, soaring from approximately 66,000 to over 205,000. Yet, this impressive growth masks a critical weakness: the number of Professional Engineers (PEs), those with the coveted ‘Ir.’ title who are authorised to sign off on projects, has failed to keep pace, creating a bottleneck that could stifle national development.